Markers of immunosenescence in CMV seropositive healthy elderly adults - Rodríguez, Ivón Johanna; Parra-López, Carlos Alberto (Frontiers in Aging, 2025)
A significant increase in life expectancy has accompanied the growth of the world’s population. Approximately 10% of the global population are adults over 60, and it is estimated that 2050 this figure will double. This increase in the proportion of older adults leads to a more significant burden of age-related diseases. Immunosenescence predisposes elderly individuals to a higher incidence of infectious and chronic non-communicable diseases with higher mortality rates. Despite advances in research, it is necessary to evaluate the cellular characteristics of the aging immune system in populations with a high incidence of latent viruses such as cytomegalovirus (CMV). In this sense, this work aimed to identify senescence markers in cells of the innate and adaptive immune system in healthy older adults with CMV infection. We observed that older adults present an increase in the population of CD14+CD16+ intermediate monocytes, an expansion of CD56neg NK cells with an increase in the expression of CD57, as well as a decrease in the naïve CD4+ and CD8+ T cells, accompanied by an increased expression of senescence markers CD57 and KLRG1 in effector CD8+ T cells.